Determining the need for rescue intracytoplasmic sperm injection in partial fertilisation failure during a conventional IVF cycle. (29th February 2016) - Cao, S.; Wu, X.; Zhao, C.; Zhou, L.; Zhang, J.; Ling, X.
Summary: To explore the need for rescue intracytoplasmic sperm injection (ICSI) in cases of partial fertilisation failure during a conventional in vitro fertilisation cycle, rescue ICSI was performed for cycles with a fertilisation rate of <50%. The data were divided into three groups based on the fertilisation rate: group 1 (0%), group 2 (<25%) and group 3 (>25%). The impact of rescue ICSI on each group was then analysed in terms of ovum fertilisation, embryo development, embryo utilisation and selection of embryos for transfer. Rescue ICSI was performed on 1831 unfertilised oocytes from 313 cycles. The fertilisation rates for group 1, group 2 and group 3 were 74.66, 68.35 and 65.46%, and the rate of polyploidy in the three groups was 8.55, 11.33, and 14.47%. The percentage of embryos that can be transferred from rescue ICSI for group 2 was 38.33%, and this value was higher than those of the other two groups. It is concluded that rescue ICSI is not recommended for patients with an IVF rate of >25% as the procedure is associated with a greater risk and low returns. However, it is feasible to perform rescue ICSI for patients with IVF rates of <25%.